Selected personality traits of nurses and flexibility in coping with stress - a moderating role of age and seniority - Martyna Jolanta Janicka; Małgorzata Anna Basińska; Michalina Sołtys (Nofer Institute of Occupational Medicine, 2020)
Background The results of numerous studies indicate that the nurse profession is burdened with an increased risk of feeling stressed and experiencing professional burnout. Effective coping with stress can protect against professional burnout as well as impact on patient care. These effects may be influenced, e.g., by personality traits. By the study, the authors decided to check whether personality traits such as empathy, impulsiveness and venturesomeness would play a predictive role for flexibility in coping with stress. Material and Methods By the study, the authors analyzed the results obtained from 137 nurses. The following research tools were used: the Impulsiveness-Venturesomeness-Empathy Questionnaire by Eysenck and Eysenck, in the Polish adaptation by Aleksandra Jaworowska, and the Flexibility in Coping with Stress Questionnaire (FCSQ-14) by Małgorzata Basińska et al. Both tools were characterized by satisfactory statistical properties. By addition, the respondents completed a personal survey which allowed collecting basic personal data. Results Venturesomeness positively correlated with flexibility in coping with stress and all its dimensions (strategy repertoire, strategy variability and reflexivity) at the low level. Similar dependencies for empathy and impulsiveness were not shown. Similarly, in assessing the predictive role of selected personality traits for flexibility in coping with stress, only venturesomeness turned out to be an important predictor. Although the model turned out to be statistically significant, it allowed explaining the variability of flexibility only in 7%. Conclusions There was a low statistically significant relationship between the nurses' venturesomeness and their flexibility in coping with stress. Empathy and impulsiveness did not play a predictive role for flexibility in coping with stress. Med Pr. 2020;71(4):451-9